UJI EFEKTIFITAS PENGOLAHAN AIR LIMBAH RUMAH SAKIT PERTAMEDIKA MENGGUNAKAN SISTEM BIOFILTER AEROB-ANAEROB - Encik Weliyadi (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2016)
The hospital wastewater contains high organic matter and can cause the quality of water to deteriorate and affects aquatic ecosystems. The objective of this study was to design a wastewater treatment unit using aerobic-anaerobic biofilter system by examining the content of turbidity, TDS and TSS. This research was conducted from January to March 2016 at Pertamedika Hospital Tarakan. The results of study showed that the concentration of turbidity, TSS and TDS decreased 48%, 56% and 11% respectively. It can be concluded that the wastewater treatment unit by using anaerobic-aerobic biofilter system was quite effectively to reduce the concentrations of turbidity and TSS. However, the concentration of TDS has not shown a significant decrease after treatment. Keyword : Wastewater Treatment unit, Aerob-Anaerob Biofilter